2014
DOI: 10.1590/1806-9282.60.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Estimated hospitalizations attributable to Diabetes Mellitus within the public healthcare system in Brazil from 2008 to 2010: study DIAPS 79

Abstract: Objective: to estimate the number of hospitalizations attributable to diabetes mellitus (DM) and its complications within the public healthcare system in Brazil (SUS) and the mean cost paid per hospitalization. Methods: the official database from the Hospital Information System of the Unified Health System (SIH/SUS) was consulted from 2008 to 2010. The proportion of hospitalizations attributable to DM was estimated using attributable risk methodology. The mean cost per hospitalization corresponds to direct med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
12

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 24 publications
(34 reference statements)
0
17
0
12
Order By: Relevance
“…In general, hospitalizations happened in the presence of DM complications [27][28][29] . In Brazil, from 2008 and 2010, DM reached around 1.3 million hospitalizations in the public network; thus, it is responsible for 8 to 12% of the hospital expenses from SUS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, hospitalizations happened in the presence of DM complications [27][28][29] . In Brazil, from 2008 and 2010, DM reached around 1.3 million hospitalizations in the public network; thus, it is responsible for 8 to 12% of the hospital expenses from SUS.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, from 2008 and 2010, DM reached around 1.3 million hospitalizations in the public network; thus, it is responsible for 8 to 12% of the hospital expenses from SUS. Of the total, 10.6% of hospitalizations were owing to diabetes itself, and 36.6% were associated with chronical complications of the disease 29 . The NHS showed that 13.4% of those who mentioned diabetes had already been hospitalized, and this frequency tended to be higher in younger, less educated, and nonwhite men.…”
Section: Discussionmentioning
confidence: 99%
“…This situation has generated high social and financial costs for the patient and for the healthcare system. Rosa et al 7 estimated that DM accounted for 12.0% of the total hospitalizations not related to pregnancies and for up to 15.4% of hospital costs of the Brazilian Public Health System (SUS) in the period from 2008 to 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Quanto a terapêutica denota-se a necessidade da elaboração de ações de saúde na prevenção de doenças crônico-degenerativas, baseado na interação multidisciplinar como proposto pela Diretriz Brasileira de Diabetes, e pautado no tratamento medicamentoso aliado ao tratamento não-medicamentoso, ou seja, a prática de exercícios físicos, um instrumento promotor de grandes benefícios para aqueles indivíduos diabéticos. A prevenção do diabetes e de suas complicações é hoje prioridade de saúde pública (12)(13)(14) . É um desafio para a equipe de saúde a adesão dos familiares e cuidadores à terapêutica, por modificações em seu modo de viver em prol do tratamento.…”
Section: Exame Físico Segundo O Método Soapunclassified